Translation and validation of the Nature Relatedness Scale to German - Gallus, Viviane; Hucke, Christine Ida; Butter, Katja; Ohlmeyer, Martin; van Thriel, Christoph (Frontiers in Psychology, 2024)
We translated the Nature Relatedness Scale, consisting of three subscales (NR-Self, NR-Perspective, NR-Experience) to German. We collected 251 data sets and performed a confirmatory factor analysis, followed by an exploratory factor analysis. The analyses revealed that the reliability of the German NRS as a whole was good. However, they also showed NR-Perspective to be the weakest factor, and that NR-Self was a rather vague construct, closely connected to the other two subscales. Overall, we came to the conclusion that the NRS' three subscales are not as distinct and reliable as expected, and instead suggest a two-factor solution (NR-Presence and NR-Perspective) for use in German.